Insights into abusive workplace behavior - Tziner, Aharon; Bar-Mor, Hadara; Shwartz-Asher, Daphna; Shkoler, Or; Geva, Lilach; Levi, Haim (Frontiers in Psychology, 2023)
Objectives This paper explores definitions, incidences, and outcomes of workplace abuse – a widespread, worldwide social phenomenon impinging on the well-being of workers in a developing labor market – and possible directions for delineating and standardizing classifications of the phenomenon that facilitate workers’ protection. Furthermore, we employ Tepper’s Abusive Supervision Survey Questionnaire [ASSQ] to identify managerial abuse in organizations regarding the type of organization (public/private), gender of the perpetrator, gender of the target, and the managerial role, of each of the abuse items. Finally, we suggest directions for further research and practical measures designed to facilitate the diminution of behavioral abuse in the workplace in the foreseeable future. Hypotheses No hypotheses are submitted in this exploratory paper. Methods Employees of two large organizations (the Katzrin Local Council and Tigbur Ltd.) and another small national organization in Israel were approached, requesting their assistance in this investigation. We introduced the questionnaire, noting its anonymity and the academic context, and that subject participation was voluntary. The questionnaire consisted of fifteen statements on a five-point response scale ranging from 1 = “I cannot remember him/her ever using this behavior with me” to 5 = “He/she uses this behavior very often with me” (alpha = 0.97, M = 1.81, SD = 1.03). One hundred five respondents comprised the final sample: men (39%) and women (61%) aged 23–66. 66.7% of the respondents were employed in a public organization, 28.5% in a private organization, and 4.8% in a national organization. Years of education: less than 12 (14.3%); 12 full years (17.1%); tertiary education (10.5%); bachelor’s degree (40%); and master’s degree and above (18.1%). While 28.6% held managerial positions, 71.4% did not. Job tenure ranged between 0.5 and 42 years. The participants in national and private organizations were combined to avoid the problem of unbalanced groups. Notably, the gender balance of the managers was men (50.5%) and women (49.5%). To ensure statistical validity, we conducted a factor analysis and performed Pearson correlations to examine the relationships between the general latent variable and the abuse items and their intercorrelations. Additionally, we conducted t-tests for independent samples (with Bonferroni corrections for multiple comparisons: see, for example) to compare (1) the respondent’s gender; (2) manager’s gender; and (3) the managerial role with each of the abuse items, and (4) the type of organization (private/public); including the general abuse variable. Results High, positive, and significant correlations were recorded between each questionnaire item and the total score of abusive behavior. The results ranged from r = 0.92 for the statement, “Puts me down in front of others” (r = 0.92) to r = 0.69 for the statement, “Does not allow me to interact with my co-workers” (r = 0.69). Reported abuse in the respondents’ organizations was relatively low (1.81), while among women managers marginally less than their male equivalents (in absolute value, the mean difference in the mean scores fell between 0.28 and 1.25). Abusive behavior in private organizations was more prevalent than in public concerns. Not surprisingly, workers reported more incidents of abuse than managers: in absolute value, the mean difference between employees and managers fell between 0 and 0.67 in the mean scores. Women reported fewer abusive behavior incidents than men; however, the differences found were insignificant. Conclusion The reports of abusive behaviors were meager. Explanations include: (1) Any instance of alleged workplace abuse can be interpreted variously by different individuals, a function of subjective perceptions and interpretations of objective data informed by several internal and external factors impinging on workers’ wellness at work. (2) The extant “trust gap,” which is part of the pervading culture, mitigates against honest reporting of workplace abuse for fear of reprisals. (3) A single report of behavioral abuse at work may be attributable to the same perpetrator repeating the aggression several times. The lower incidence of reported abuse among female managers could be understood in line with studies that indicate that men display aggression more frequently than women playing out their expected respective stereotypical roles in society. Furthermore, following women reflect more stable personality dispositions and are less likely than men to aggress against others without provocation. In line with these observations, women’s management style projects “an ethics of care,” focusing on interpersonal relations and a greater tendency than male managers toward cooperation, creativity, innovation, and shared decision-making. Because the differences found in all the variables in our investigation investigated were not significant, we cannot conclude that the results indicate a trend. Finally, we assume that appropriate sanctions against perpetrators at the workplace and regulation in public organizations would reduce the incidence of workplace abuse. In a more optimistic vein, we recommend that management and HR personnel initiate positive measures to raise awareness of behavioral abuse and eliminate it from their organizations. They should initiate training workshops, events, and support groups akin to those extant in organizations focused on eliminating racial prejudice and advocating sustainability and wellness in the workplace. Ultimately, the goal is to protect workers’ dignity, the integrity of the organizations, and the welfare of society.